SOCIAL PROTECTION AS ONE OF THE ACTIVITIES BY MODE OF TRANSPORT - Hladchuk, O. O. (Science and Transport Progress, 2007)
The leadthrough of monitoring researches is offered for determination of complex estimation of social protected of workers of railway transport. The tasks and stages of this procedure are examined.